Preparation and optimization of ibuprofen-loaded nanoemulsion formulation - Shahidan, Nur Shahidah (Journal of Multidisciplinary Engineering Science and Technology (JMEST), 2019)
Nanoemulsion containing ibuprofen was developed. However, the composition and method to prepare nanoemulsion were not consistent and needed to be optimised. In this study, nanoemulsion containing a mixture of palm kerneloil esters (PKOE), ibuprofen,Tween 80 (T80), and water was modified from the previous report. It was prepared by a combination of two methods, including low energy and high energy emulsification methods. The composition of nanoemulsion was optimised by a Mixture of Experimental Design (MED), where PKOE, T80, and water were set as variables while droplet size was a response. A total of 15 run experiments were evaluated. An optimum formulation was validated, and the composition of 3.0 wt % of PKOE, 15.0 wt% of Tween 80, 2.0 wt % of ibuprofen and 80.0 wt. % of water with the droplet size of 97.26 nm was obtained.The formulation is stable in the storage at room temperature (25 ± 2 ºC) within 3 months against coalescence process. The polydispersity index and zeta potential of the optimized formulation were 0.271 and -19.8 mV, respectively.